2002
DOI: 10.1063/1.1502919
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic entropy change and its temperature variation in compounds La(Fe1−xCox)11.2Si1.8

Abstract: Magnetic entropy change ΔS of compounds La(Fe1−xCox)11.2Si1.8 with the cubic NaZn13-type structure was investigated around their Curie temperature TC. It is found that the phase transition is completely reversible, indicating a nature of second order phase transition. The maximum value of |ΔS|∼13.0 J/kg K under a field of 5 T was achieved in compound LaFe11.2Si1.8 at its TC of ∼222 K, which exceeds that of most materials involving a second order transition at the corresponding temperature. With increasing subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…The temperature step of 2 K is chosen in the vicinity of T C and a step of 5 K for the regions far away from T C . For the samples of LaFe 11.2 Si 1.8 [17] and La 07 Pr 0.3 Fe 10.4 Co 0.8 Si 1.8 , no magnetic hysteresis is observed, while the La 07 Pr 0.3 Fe 11.2 Si 1.8 compound shows a very small magnetic hysteresis at T C as shown in Fig. 3b.…”
Section: Methodsmentioning
confidence: 71%
See 1 more Smart Citation
“…The temperature step of 2 K is chosen in the vicinity of T C and a step of 5 K for the regions far away from T C . For the samples of LaFe 11.2 Si 1.8 [17] and La 07 Pr 0.3 Fe 10.4 Co 0.8 Si 1.8 , no magnetic hysteresis is observed, while the La 07 Pr 0.3 Fe 11.2 Si 1.8 compound shows a very small magnetic hysteresis at T C as shown in Fig. 3b.…”
Section: Methodsmentioning
confidence: 71%
“…Isotherms on field increase and decrease are shown only at T C in a field rang of 0.a completely reversible variation of magnetization with temperature. This is a characteristic of second-order transition, as shown in LaFe 11.2 Si 1.8[17]. The Curie temperature T C is 216, 203 and 290 K for LaFe11.2 Si 1.8 , La 07 Pr 0.3 Fe 11.2 Si 1.8 and La 07 Pr 0.3 Fe 10.4 Co 0.8 Si 1.8 , respectively.…”
mentioning
confidence: 95%
“…Magnetic materials with large MCEs were thought to be promising candidates as magnetic refrigerants. In the field of the near room temperature magnetic refrigeration, much attention has been paid to the LaFe 13−x Si x (1.2 ≤ x ≤ 1.6) alloys and their related compounds because of their large MCEs, cheap raw materials and adjustable Curie temperature (T c ) [3][4][5][6][7][8][9]. Fujita and other researchers [10][11][12][13] studied the effect of interstitial hydrogen on LaFe 13−x Si x alloys, and it was found that the T c of the LaFe 13−x Si x alloys could be adjusted to near room temperature by hydrogenation treatment and the large magnetrocaloric * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…However, the Curie temperatures of these compounds are usually much lower than the room temperature, and therefore many studies have been carried out to enhance the T C . It has been demonstrated that the Curie temperature of these compounds can be tuned to room temperature by substituting Co for Fe or by introducing the interstitial elements H, C and B into the lattice [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%